Evaluation of Resistance to Root Aphid in some Sugar Beet Cultivars and its Effect on their Quantitative and Qualitative Yields - Heydar Azizi; Esmaiel Alizadeh; Valiollah Yousefabadi; Hamed Mansouri (پژوهشنامه اصلاح گیاهان زراعی)
Extended Abstract Background: About 30% of the world's sugar needs are provided by sugar beet and sugar cane. Many biotic factors, such as pests, diseases, and weeds, decrease production and damage sugar beet fields. To bring sugar beet production to its real potential and maintain it at this level, it is necessary to identify biotic stress-causing factors, determine their individual role in reducing the yield, and investigate their management and control methods. One of the pests of sugar beet is the root aphid that settles on the secondary roots and causes dwarfism and wilting of the plants by feeding on plant sap. It also causes a decrease in root weight and a 30-36% decrease in sugar content. Due to the special conditions of the aphid's life under the soil, the effect of the aphid’s white wax secretions on soil non-wetting by the poison solution, and the lack of a suitable systemic poison, the use of chemical poisons in the form of soil-water is not recommended in controlling this pest. Therefore, the most effective method for managing this pest in sugar beet fields is to use resistant and tolerant cultivars. Therefore, this research aimed to evaluate the resistance of domestic and foreign cultivars to this type of aphid. This study also investigates the effect of this pest on their quantitative and qualitative yields to use them or their ancestors in future breeding programs to produce resistant cultivars. Methods: The resistance to root aphid of eight sugar beet cultivars (Asia, Arta, Dena, Shokoofa, biopolymerized Shokoofa, Nika, Palma, and BTS505) and the effect of this pest on their quantitative and qualitative yields were evaluated in a pilot experiment based on a randomized complete block design with four replications in the West Azarbaijan Agricultural and Natural Resources Research Center, agricultural education center of Miandoab city, in 2023 crop season. To this aim, sugar beet root aphid was sampled by harvesting 20 sugar beet roots (four replicates per cultivar) in the middle of September. The samples were grouped into four resistant, semi-resistant (tolerant), sensitive, and very sensitive groups based on the percentage of sugar beet roots infected with aphids.  Traits related to quantitative and qualitative yields were also measured after harvesting. Results: The results of the analysis of variance showed that the effect of the cultivar was significant on all measured traits (p ≥ 0.01). The highest and lowest values of the genotypic and phenotypic coefficients of variation belonged to the percentage of aphid-infected roots (46.52% and 46.73%, respectively) and the sugar extraction coefficient (4.55% and 4.69%, respectively). Based on the results from mean comparisons for the cultivars, the highest and lowest values of the root yield trait was measured in BTS505 and Palma foreign cultivars with 82.35 and 62.81 t.ha-1, respectively, which were placed in two statistical groups. However, the average root yield of the Palma cultivar with the lowest root yield was not significantly different from the Shokoofa cultivar (64.41 t.ha-1). The highest sugar content trait belonged to the BTS505 foreign cultivar (16.86%), and the lowest values were obtained for the Palma foreign cultivar and the Shokoofa domestic cultivar (12.65 and 13.01%, respectively). No significant differences were observed between the domestic and foreign cultivars in the averages of the root yield trait (69.56 and 72.58 t.ha-1, respectively) and sugar content (14.25 and 14.75%, respectively). This indicates the genetic progress of the newly introduced domestic hybrid cultivars in terms of these two important traits that influence the final yield of sugar. In terms of the percentage of aphid-infected roots, the studied cultivars were placed in three statistical groups. As such, BTS505 and Asia cultivars with the lowest infection percentage were in the first group (as resistant cultivars), Arta, Dena, biopolymerized Shokoofa, and Nika cultivars with moderate levels of infection were assigned to the second group (as semi-resistant or tolerant cultivars), and two cultivars, Palma and Shokoofa, were placed in the third group as sensitive cultivars. Conclusion: The use of chemical pesticides to control this pest should be reduced due to environmental, health, and economic considerations. On the other hand, the improper efficiency of many available pesticides necessitates the use of resistant and tolerant varieties of sugar beet to this pest (BTS505 and Asia as resistant cultivars) as the main management solution. Due to their genetic resistance to rhizomania and nematode diseases, they can be used for cultivation in many beet-growing areas of Iran. However, it is suggested to compare more different cultivars to be examined and evaluated in different years and places with different climatic conditions, which can finally be recommended with more confidence.